B BARRIER DAN SELF-EFFICACY APOTEKER DALAM PROMOSI KESEHATAN DI FASILITAS KESEHATAN TINGKAT PERTAMA KOTA BANJARBARU: BARRIER DAN SELF-EFFICACY APOTEKER DALAM PROMOSI KESEHATAN DI FASILITAS KESEHATAN TINGKAT PERTAMA KOTA BANJARBARU - Nurul Mardiati; Elsa Munajad; Rahmi Hidayati (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Introduction: Health promotion is more focused on maintaining and increasing the degree of well-being rather than returning health due to illness or accidents. The barrier is an obstacle or obstacle experienced by the pharmacist in carrying out health promotion, while self-efficacy, also known as self-confidence, is a good attitude that a person has when they are confident in their ability to form positive judgments about both themselves and their environment. Objective: The purpose of this study is to characterize the barriers to health promotion, as well as self-efficacy in doing so, and the relationship between the two. Methods: Using a cross-sectional design, this study's respondents were. After distributing questionnaires to 20 pharmacists, a purposive sample method was used to choose the participants. Results: In the Banjarbaru City FKTP, the majority of pharmacists—13 individuals, or 65%—have a high barrier to health promotion. Lack of time (70%) and the absence of uniform standards for pharmacists (65%) are major obstacles. The majority of pharmacists, or 12 individuals, also exhibit strong self-efficacy. When pharmacists who work at the Banjarbaru City FKTP promote health, there is a correlation between obstacles and self-efficacy. Conclusion: In order to undertake health promotion, there is a relationship between the barrier and self-efficacy.